Profile of Skin Disorders in Unreached Hilly Areas of North India - Deepak Dimri; Venkatashiva Reddy B; Amit Kumar Singh (Dermatology Research and Practice)
Background. The pattern of skin morbidity in an area depends on climate, geography, socioeconomic status, nutrition, genetics, and habits of the community. Objective. The objective of the present study was to describe the morbidity profile of patients attending dermatology outpatient department in a tertiary care centre of Garhwal hills, North India. Methodology. This is a record based study carried out using the morbidity registers. Patient details, diagnosis, and treatment provided by physicians were documented in the morbidity register. ICD coding was done to categorize the patients. Results. The total number of new episodes of illnesses treated in the skin outpatient department during 2009–2014 was 47465. Adults (>18 years) constituted about 80.9%. Among adults, about 59.9% were males. Overall the infections of the skin and subcutaneous tissue were the most common (32.6%) followed by the disorders of skin appendages (19.8%), and dermatitis and eczema (18.8%). Of the total patients 16.9% were affected by dermatitis and 16.7% by acne. Psoriasis, urticaria, melasma, and vitiligo were present in 3.4%, 3.4%, 3.6%, and 3.3% patients, respectively. Conclusion. This knowledge will help in planning appropriate range services to meet the patients’ needs and help in training of health staff to meet these needs.